Efectos tóxicos del aluminio: una intoxicación silenciosa - Yucra Sevillano, Sandra (2024)
Objective: To describe, on the basis of established norms of scientific literature, the sources of aluminum (Al3+) intake, its metabolism in the human body, its toxic effects, and its relationship with some neurological diseases. Materials and Methods: A non-systematic search of pertinent literature was conducted in PubMed, Elsevier, SciELO, Springer Link, Web of Science, and Google Scholar. Results: Sources of aluminum intake included food cooked with aluminum foil, medications, and traditionally used clays (known as “chacco”) in Southern Peru. It is estimated that the average person ingests 3-5 mg of Al3+ per day. Approximately 40% of the ingested Al3+ is retained in the intestinal coverage or secreted by the enterocytes into the circulatory system. This elevates the aluminum body levels and allows it to enter into several organs, including bones and brain. Aluminum's toxic effects occur due to high levels interfering with different biological and enzymatic mechanisms. Clinical conditions associated with aluminum intoxication include Alzheimer's disease, Amyotrophic Lateral Sclerosis, chronic kidney disease, and others. Conclusions: Aluminum has been implicated in the development of both neurodegenerative and non-degenerative diseases. Its capacity to be latently stored in several tissues and organs is considered as the main etio-pathogenic mechanism.